Improving Thermal and Electric Energy Efficiency at Cement Plants : International Best Practice - International Finance Corporation (Washington, DC, 2017)
Cement is paramount for economic development and poverty reduction in emerging markets. Along with aggregates and water, cement is the key ingredient in the production of concrete, and, as such, is an essential construction material that enables large infrastructure projects in energy, water, and transport, as well as, importantly, the construction of modern buildings and urban infrastructure. Given the rapid urbanization rates in developing countries, cement is crucial for delivering on the climate-smart cities agenda. Emerging markets have been rapidly increasing their cement use and now account for over ninety percent of cement consumption worldwide. This report and an accompanying report on alternative fuels provide a summary of international best practice experience in the cement sector and focus on specific technical measures that could be implemented by cement plants to reduce their operating costs and improve their carbon footprints. The reports provide a plethora of practical information from implemented projects and include detailed technical descriptions, capital and operating costs, and case studies and references from locations where the measures have been implemented. A combination of general and in-depth information will make these reports a helpful read to both management and technical and operating personnel of cement plants as well as to a larger range of stakeholders.